Pharmaceutical Biotechnology Fundamentals and Applications - Crommelin, Daan J. A.; Sindelar, Robert D.; Meibohm, Bernd; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This introductory text explains both the basic science and the applications of biotechnology derived pharmaceuticals, with special emphasis on their clinical use. It serves as a complete one-stop source for undergraduate/graduate pharmacists, pharmaceutical science students, and for those who did not receive formal training in this field. Pharmaceutical Biotechnology: Fundamentals and Applications, Fifth Edition completely updates the previous edition, and includes additional coverage on newer approaches such as oligonucleotides, mi/siRNA, gene therapy and advanced therapeutics. Daan J.A. Crommelin is Professor Emeritus Department of Pharmaceutical Sciences, Utrecht Institute for Pharmaceutical Sciences at Utrecht University, Utrecht, The Netherlands and Adjunct Professor in the Department of Pharmaceutics and Pharmaceutical Chemistry at the University of Utah, Salt Lake City, UT, USA Robert D. Sindelar is Professor and former Dean Faculty of Pharmaceutical Sciences and The Centre for Health Evaluation & Outcomes Sciences (CHEOS), The University of British Columbia (UBC), Vancouver, BC, Canada and President of the Global Drug Commercialization Centre (GDCC)-China and Vice-President GDCC-worldwide, Chengdu, China Bernd Meibohm is Professor of Pharmaceutical Sciences and Associate Dean for Research and Graduate Programs at the University of Tennessee Health Science Center, College of Pharmacy, Memphis, TN, USA.
Molecular Biotechnology -- Biophysical and biochemical analysis of recombinant proteins -- Production and downstream processing of biotech products -- Formulation of biotech products, including biopharmaceutical considerations -- Pharmacokinetics and pharmacodynamics of peptide and protein drugs -- Immunogenicity of pharmaceutical proteins -- General considerations of monoclonal antibodies from structure to therapeutic application -- Genomics, Other (3z(BOmics(3y (BTechnologies, Personalized Medicine and Additional Biotechnology-Related Techniques -- Dispensing biotechnology products: handling, professional education and product information -- Economic considerations in medical biotechnology -- Regulatory framework for biosimilars -- Vaccines -- Oligonucleotides and siRNA -- Gene therapy -- Stem cell technology -- Therapeutic Applications.-Endocrinology -- Insulin -- Follicle-stimulating hormone -- Growth hormone -- Cardiovascular and Respiratory Applications -- Recombinant coagulation factors and thrombolytics -- Recombinant human deoxyribonuclease -- Oncology -- Monoclonal antibodies in oncology -- Hematopoetic growth factors -- Inflammation and Immunemodulation -- Monoclonal antibodies in transplantation -- Monoclonal antibodies and antibody-based therapeutics in anti-inflammatory therapy -- Interferons and interleukins -- Anti-infectious diseases -- Monoclonal antibodies -- Enzyme replacement therapy.s
Keywords: Pharmaceutical technology; Biomedical engineering; Pharmaceutical Sciences/Technology.; Biomedical Engineering/Biotechnology.